Running economy in elite soccer and futsal players: differences among positions on the field - Santos-Silva,Paulo Roberto (2017)
OBJECTIVE: To determine running economy in a large sample of elite soccer and futsal players to obtain benchmarks in different positions. METHODS: Running Economy is the energy demand at a submaximal running velocity. Players were divided into 6 subgroups. Soccer: defenders, midfielders, and strikers; futsal: defenders, wingers, and pivots. Elite soccer players (n=129) and elite futsal players n=72 performed an incremental running test starting at 8.4 km.h-1 with increments of 1.2 km.h-1 every two minutes on a treadmill until exhaustion. Running Economy was determined by interpolation between ventilatory thresholds 1 and 2 (VT1 and VT2). RESULTS: Running Economy (measured as mL.kg-1.km-1) was compared between the playing positions in the two team sports. In soccer, running economy was 222.7 (defenders), 227.0 (midfielders), and 219.8 (strikers) mL.kg-1.km-1, respectively. In futsal, the corresponding values were 198.5 (defenders), 196.9 (wingers), and 190.5 (pivots) mL.kg-1.km-1, respectively. We no found significantly differences between the three positions in both sports. The Running Economy of futsal players was 12.5% better than that of soccer players. Running Economy correlated positively with oxygen uptake at VT2 in both sports and in all positions. CONCLUSION: Futsal players exhibited better Running Economy than soccer players; this should be considered as a factor in the athlete's training plan.